Abnormal gray matter asymmetry in alcohol dependence. Issue 9 (13th June 2018) - Zhu, Jiajia; Wang, Yajun; Wang, Haibao; Cheng, Wenwen; Li, Zipeng; Qian, Yinfeng; Li, Xiaohu; Li, Xiaoshu; Yu, Yongqiang
Abstract : Previous voxel-based morphometry studies have provided evidence that patients with alcohol dependence (AD) have widespread gray matter morphological abnormalities. However, brain structural asymmetry in AD has not been assessed to date. Here, we aimed to use a recently developed voxel-based morphometry-based approach to investigate global and regional gray matter asymmetry alterations in AD. A total of 39 male individuals, including 19 AD patients and 20 age-matched healthy controls, underwent high-resolution structural MRI. Global and voxel-wise gray matter asymmetries were measured separately by the Dice coefficient and the asymmetry index, which were compared between the two groups. We found no difference in the global gray matter asymmetry between AD patients and healthy controls. However, voxel-wise gray matter asymmetry analysis showed that AD patients and healthy controls had different distribution patterns of brain regions with a rightward asymmetry and a leftward asymmetry Furthermore, we observed an increased rightward asymmetry of gray matter in the hemispheric I–IV and V of the cerebellum and lingual gyrus in AD patients. These findings suggest that abnormal structural asymmetry in the cerebellum and the primary visual cortex may be the neural mechanisms contributing toward motor and visual impairments in AD.